Common Complications in Infants Born to Diabetic Mothers : Complications in Infants Born to Diabetic Mothers - Shah, Syed Bawar; Bawar, Shandana; Wajeeha, .; Farooq, Nazish (Pakistan Journal of Health Sciences, 2024)
Infants of diabetic mothers are at increased risk of complications. There is always a need for more research on this topic to look for complications and make strategies for prevention and management. Objectives: To determine the frequency of complications in infants born to diabetic mothers. Methods: This descriptive study was done at the Department of Pediatrics, Molvi Ameer Shah Memorial Hospital, Peshawar from 1st January 2022 to 31st December 2022. A total of 150 infants born to diabetic mothers were enrolled after written informed consent and frequencies of complications were noted. Data were analyzed using SPSS 24.0. Results: The mean age of the patients was 3.08 ± 1.7 days. The minimum age was 1 day, and the maximum was 7 days. The mean age of the mother was 26.9 ± 4.07 years. The mean gestational age was 36.9 ± 1.4 weeks. The mean duration of diabetes was 7.6 ± 1.14 years. The mean HbA1c level was 7.27 ± 2.41. There were 38% males and 62% female. Adequate diabetic control was present in 24.7% of patients while 75.3% had poor diabetic control. The most common complication was hypoglycemia in 24.7% followed by Macrosomia in 22.7%, prematurity in 20%, hyperbilirubinemia 11.3%, hypocalcemia in 10.7% and polycythemia in 10.7% patients. Conclusions: Most common complication was hypoglycemia followed by macrosomia, prematurity, hyperbilirubinemia, hypocalcemia, and polycythemia. However, due to its limited sample size, the results may not be generalizable.